2014
DOI: 10.5301/grhta.2014.12359
|View full text |Cite
|
Sign up to set email alerts
|

New Oncological Drugs: Analysis of Survival Gain

Abstract: lon retto (9,7%). Il cancro allo stomaco viene al quarto posto (7,8%); da notare che, nelle prime stime del 1975, esso rappresentava invece la neoplasia più diffusa. Segue il cancro alla prostata (7,2%), con circa tre quarti dei casi registrati nei Paesi a sviluppo avanzato.Passando dall'incidenza alla mortalità, si stimano 7,6 milioni di decessi. Anche qui, il cancro ai polmoni è al primo posto come fattore causante (18,2%). Seguono poi il cancro allo stomaco (9,7%), quello al fegato (9,2%), quello al colon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…After inspection of the abstract or the full text of these articles, a total of eight studies [Martone et al . 2014a, 2014b; Schnipper et al . 2015; Ebara et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After inspection of the abstract or the full text of these articles, a total of eight studies [Martone et al . 2014a, 2014b; Schnipper et al . 2015; Ebara et al .…”
mentioning
confidence: 99%
“…Our first extraction of eligible papers from PubMed selected a total of 258 citations. After inspection of the abstract or the full text of these articles, a total of eight studies [Martone et al 2014a[Martone et al , 2014bSchnipper et al 2015;Ebara et al 2013;Shiroiwa et al 2011;Tsuchiya et al 2011;Mouri et al 2013;Österlund et al 2014] were found to satisfy the inclusion criteria; these articles referred to the following four countries: Italy, US, Japan and Scandinavia. Figure 1 (panels a through d) illustrates the results of our analyses.…”
mentioning
confidence: 99%
“…Non escludiamo di avere male interpretato qualche passaggio dell'articolo di Ballatori e colleghi, ma a nostro avviso sarebbe invece interessante incorporare nel calcolo una soglia. Su questo punto, inoltre, potrebbe essere interessante un confronto con la precedente letteratura (8)(9)(10)(11)(12).…”
Section: Il Beneficio Dei Farmaci Oncologici: Commento All'articolo Dunclassified